Knowledge and practice modifications regarding COVID-19 among dental practitioners of Nepal - Ranjit, Rebicca; Manandhar, Pratik; Bista, Soni; Ranjit, Elijma (Birat Journal of Health Sciences, 2021)
Introduction: COVID-19 has adversely gridlocked many sectors including dentistry. A good knowledge regarding the disease eventually determines the preparedness of dentists to provide relatively safe dental services. Objectives: This research was conducted to evaluate knowledge and relevant practice modifications among dental practitioners of Nepal during COVID-19 pandemic. Methodology: A cross-sectional online questionnaire survey was conducted among dental practitioners of all the provinces of Nepal. They were enquired for sociodemographic details and their knowledge, and the modifications they adopted while practising dentistry during this pandemic. The scores were summed up, and mean scores for knowledge and practice were calculated respectively which were further expressed as a percentage. Inferential statistics (Independent t-test and ANOVA, p < 0.05) were used to examine differences between study variables. Results: Out of 422 participants, most of them belonged to 31-40 years age group (178, 42.2%) and majority were females (246, 58.3%). Mean knowledge scores were significantly higher among practitioners of age ≥51 years, males, specialists, those working in both clinic and hospital, and those who have been practising dentistry for ≥10 years. Mean practice scores were significantly better among specialists. Conclusion: The overall mean scores for knowledge was good (81.3%) while for practice, overall mean score was poor (44.6%). The main reason behind the poor practice modifications despite good knowledge score could be the lack of minimum requirements for infection control in developing countries like Nepal.